The use of a QFD-Fuzzy approach to support investors’ decisions: A study on fast growing digital businesses in London - Costa Júnior, João Florêncio da; Cabral, Eric Lucas dos Santos; Barreto Junior , Jurandir Galdino; Severo, Ricardo Augusto Niederauer Flores; Araújo, Afrânio Galdino de (Contextus - Revista Contemporânea de Economia e Gestão, 2023)
The work analyses the growth strategy of fast-growing digital business in order to develop a QFD-Fuzzy based methodology to support investors’ decisions. Methodologically, a qualitative transversal research with the CEOs and Founders of 119 start-ups was carried out followed by the development of a QFD-Fuzzy matrix, to assess the impact of key companies’ characteristics onto strategic growth options. The authors found that number of employees and intention to raise money on a short-term basis were the least determining elements for those companies’ growth strategies, whereas having already raised funds and their growth rate were the most determining aspects that influenced their growth strategy. Also, it was shown that the QFD-Fuzzy Matrix may be adapted to support investors’ decisions.